The economic analysis of populism a selective review of the literature - Emilio Ocampo (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2019)
Although the application of the conceptual and analytical framework of economics to the study of populism is still in its infancy, great advances have been made in recent years. This paper reviews some key contributions behind this progress. When analyzing populism, economists face two methodological hurdles: lack of consensus and clarity about its definition and reconciling the populist vote with voter rationality. The former has plagued sociologists and political scientists for decades. As to the latter, it raises a conundrum: if populist policies are detrimental to economic growth, as most economists agree, the vote for a populist candidate suggests some irrationality or inefficiency in the political markets. The works reviewed in this paper propose alternative approaches to address both issues. The most promising line of research in the economic analysis of populism draws concepts from other social sciences such political theory, sociology, history and social psychology.
Keywords: B2; D72; D78; D83; H0; P47; P48; 330; Populism; political economy; voter behavior; rationality; democracy